Diversity of Symbiodiniaceae in 15 Coral Species From the Southern South China Sea: Potential Relationship With Coral Thermal Adaptability - Qin, Zhenjun; Yu, Kefu; Chen, Biao; Wang, Yinghui; Liang, Jiayuan; Luo, Wenwen; Xu, Lijia; Huang, Xueyong (Frontiers in Microbiology, 2019)
It is well known that the adaptability of coral-Symbiodiniaceae symbiosis to thermal stress varies among coral species, but the cause and/or mechanism behind it are not well understood. In this study, we aimed to explore this issue based on zooxanthellae density (ZD) and Symbiodiniaceae subclade. Hemocytometry and next-generation sequencing of the internal transcribed spacer region 2 (ITS2) marker gene were used to observe ZDs and Symbiodiniaceae subclades associated with fifteen typical coral species in the southern South China Sea (SCS). Average ZDs of all corals were in low levels, ranging from 0.84 to 1.22 × 106 cells cm–2, with a total of five Symbiodiniaceae genera, Symbiodinium, Cladocopium, Durusdinium, Fugacium, and Gerakladium, as well as 24 dominant subclades, were detected and varied among these coral species. Pocillopora verrucosa was dominated by Durusdinium (subclade D1/D1a), and other colonial corals were dominated by Cladocopium, but the subclades were varied among these species. Porites lutea and Montipora efflorescens were dominated by C15, and Echinopora lamellosa, Hydnophora exesa, and Coscinaraea exesa were dominated by C40. Acropora corymbosa, Merulina ampliata, and five species of Faviidae were mainly associated with Cladocopium types of C3u and Cspc. In contrast to other colonial corals, the dominant subclade of solitary Fungia fungites was C27, with high host specificity. Our study indicates that coral thermal stress adaptability is mainly affected by dominant Symbiodiniaceae type instead of ZD in the southern SCS. Some heat-sensitive corals, such as P. verrucosa corals, have acquired a high abundance of heat-tolerant Durusdinium to adapt to thermal stress. This could be the main reason for these corals becoming the dominant corals in this reef region. Background subclades analyses showed significant differences among coral species in subclade quantity and diversity. These suggest that numbers of coral species may have adapted to high environmental temperature by adopting various symbionts and/or associating with heat-tolerant Symbiodiniaceae.